60-Year-Old Man with Pheochromocytoma and Clinical Picture of Depression - Urszula Ambroziak (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2016)
Introduction: Pheochromocytoma is an adrenal gland tumour, which usually produces catecholamines. The classical triad of clinical symptoms consists of palpitations, headaches  nd profuse sweating. Other symptoms include: hypertension, anxiety, pallor, nausea, weakness. However, it can be asymptomatic. Because of unspecific symptoms the diagnosis of this rare neuroendocrine tumor can be missed or delayed. In differential diagnosis other entities should be considered: essential hypertension, anxiety attack, hyperthyroidism, hypogonadism, hypoglycemia, renal artery stenosis, intracranial lesion, autonomic epilepsy, carcinoid syndrome, use of cocaine or amphetamine.The final diagnosis is based on biochemical testing of urine or plasma metanephrines and imaging examination (CT, MRI). Although huge improvement in biochemical testing is observed in case of lack of symptoms or nonspecific clinical picture, false positive biochemical results should be excluded. Case: This study reports a 60-year-old man admitted to the hospital because of a left drenal tumor (35 x 30mm) found incidentally during abdominal ultrasound examination. The patient complained only of profuse sweating on exertion. He has been treated for hypertension for two years and for depression for 7 years. There was no abnormalities in physical examination. Endocrine work-up revealed elevated urine metanephrines and urine noradrenaline, observed both before and after adrenal surgery. Histopathology report confirmed pheochromocytoma. To exclude drug interferences, depression medication after surgery was withdrawn for one month and repeated results of metanephrines and    oradrenaline were normal. As the patient was in good condition with no deterioration of his  motional status clomipramin and minaserin were kept withdrawn and the patients remains without medication. Conclusion: This case report shows that clinical picture of pheochromocytoma can mimic depression. Diagnosis of pheochromocytoma in patient with depression on medication may be difficult,especially when comes to the assessment of the cure after surgery.